2009
DOI: 10.1534/genetics.109.102640
|View full text |Cite
|
Sign up to set email alerts
|

Tethering Recombination Initiation Proteins inSaccharomyces cerevisiaePromotes Double Strand Break Formation

Abstract: Meiotic recombination in Saccharomyces cerevisiae is initiated by the creation of DNA double strand breaks (DSBs), an event requiring 10 recombination initiation proteins. Published data indicate that these 10 proteins form three main interaction subgroups [(Spo11-Rec102-Rec104-Ski8), (Rec114-Rec107-Mei4), and (Mre11-Rad50-Xrs2)], but certain components from each subgroup may also interact. Although several of the protein-protein interactions have been defined, the mechanism for DSB formation has been challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
(69 reference statements)
1
13
0
Order By: Relevance
“…Several of the initiation proteins (i.e., Mre11, Spo11, Mei4, and Rec114) have been shown to be located specifically at the site of DSBs [i.e., hotspots; (Borde, Lin et al 2004;Prieler, Penkner et al 2005;Sasanuma, Murakami et al 2007)]. All ten are required for recombination initiation (Peciña, Smith et al 2002), and at least seven are able to target DSBs at a coldspot (Koehn, Haring et al 2009). These observations, in addition to the many experiments that suggest subcomplexes exist among the initiation proteins (see Introduction), support the idea that a bona fide recombination initiation complex exists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of the initiation proteins (i.e., Mre11, Spo11, Mei4, and Rec114) have been shown to be located specifically at the site of DSBs [i.e., hotspots; (Borde, Lin et al 2004;Prieler, Penkner et al 2005;Sasanuma, Murakami et al 2007)]. All ten are required for recombination initiation (Peciña, Smith et al 2002), and at least seven are able to target DSBs at a coldspot (Koehn, Haring et al 2009). These observations, in addition to the many experiments that suggest subcomplexes exist among the initiation proteins (see Introduction), support the idea that a bona fide recombination initiation complex exists.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical roles of Mre11 and Rad50 after DSB formation are relatively clear (Borde 2007), but their role in actually creating the DSB is still unknown. Mre11 associates with hotspots when all the other RIPs are present (Borde, Lin et al 2004), but from the tethering experiments presented in Chapter 2, it does not appear to be responsible for recruiting the rest of the RIPs to the DNA for initiation (Koehn, Haring et al 2009). We have not tested the ability of the other members of the MRX subcomplex (i.e.…”
Section: Future Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the above evidence suggests an order of assembly of the recombination initiation complex, Demelza Koehn's work suggests that if this order of assembly occurs, then it is not absolutely essential for function (Koehn et al, 2009). She has shown that strains with DB fusions of SPO11, REC104, REC114, REC102, REC107, MEI4 and SKI8 can all make DSBs at GAL2, suggesting that each of these proteins are capable of recruiting and forming a functional recombination initiation complex, despite presumably altering the wild type order of assembly.…”
Section: Rad50 During Mitosis Additional Two-hybrid Experiments Demomentioning
confidence: 99%
“…She found that DB-SKI8 strains made DSBs at GAL2, although not as many as DB-Spo11 (7.3% in DB-Spo11 vs. 2.2% in DB-Ski8). This indicates that SKI8 could recruit the other factors including SPO11 to the DNA and form a functional complex, suggesting that Ski8 may serve a critical role in complex formation other than being merely a scaffold protein that allows Spo11-Rec102-Rec104 association (Koehn et al, 2009).…”
Section: Ski8 Proteinmentioning
confidence: 99%